Spheroidal nano alpha-alumina and method for preparing the same
Patent Information
- Application Number
- CN202611065954.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-17
AI Technical Summary
[0009]根据以上现有技术中的不足,本发明的目的是提供一种类球形纳米α-氧化铝的制备方法,旨在解决现有制备技术中存在的工艺复杂、反应条件苛刻、煅烧温度高、最终产品易团聚、粒径分布不均等问题,从而实现一种工艺简单、适合规模化生产、能稳定制备出高品质类球形纳米α-氧化铝的方法
(1)通过氧化铝晶种诱导和形貌优化剂(形貌优化剂)的协同作用,将α-氧化铝的生成温度由传统的1150℃以上显著降低至900-1000℃区间,大幅减少了能源消耗,降低了生产成本。沉淀步骤中通过控制反应条件和使用分散剂,获得了均匀的前驱体;关键的湿磨步骤确保了形貌优化剂的微观均匀分布,避免了煅烧过程中因局部过热或助剂不均导致的晶粒异常长大。较低的煅烧温度有效抑制了颗粒间的烧结粘连,最终获得了球形度高、粒径小(纳米级)且分布窄(单分散性好)的α-氧化铝粉体。
Smart Images

Figure CN122586094B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic non-metallic materials technology, specifically to spherical nano-α-alumina and its preparation method. Background Technology
[0002] Nano-alumina, as an important advanced inorganic material, exhibits superior properties in optics, electricity, heat, magnetism, and mechanics that are not found in traditional bulk alumina due to its unique quantum size effect, surface effect, and macroscopic quantum tunneling effect. These properties make it promising for applications in high-tech fields such as electronic packaging, catalyst supports, bioceramics, precision coatings, and aerospace.
[0003] Among numerous nano-alumina products, powders with spherical or near-spherical morphologies are the preferred choice for high-end applications due to their excellent flowability, high packing density, and low specific surface energy. For example, in thermally conductive fillers, spherical particles can form more efficient thermal conduction pathways, significantly improving the thermal conductivity of polymer materials; in high-precision polishing, spherical particles can reduce scratches and achieve high-quality surface finishing; and in the preparation of advanced ceramics, spherical powders are beneficial for obtaining highly dense and uniform green bodies, thereby improving the mechanical properties of sintered ceramics.
[0004] Currently, methods for preparing nano-sized spherical alumina are mainly divided into liquid-phase methods and gas-phase methods. Gas-phase methods, such as spray pyrolysis and plasma methods, can produce powders with good morphology, but they typically involve huge equipment investments, high energy consumption, and low yields, limiting their large-scale industrial application. Liquid-phase methods, such as sol-gel methods, hydrothermal methods, microemulsion methods, and precipitation methods, have been widely studied due to their relatively simple processes and lower costs. However, these liquid-phase methods still face many challenges in practical applications: Process complexity and harsh conditions: For example, hydrothermal processes usually need to be carried out in reactors with high temperature and high pressure (typically >150℃, >1MPa), which places high demands on the safety and corrosion resistance of the equipment, increasing production risks and costs.
[0005] Particle agglomeration and morphology disruption: During the subsequent drying and high-temperature calcination processes, the fine nanoparticles of the precursor prepared by the liquid-phase method are prone to hard agglomeration and sintering adhesion. This phenomenon not only destroys the original spherical morphology of the particles, but also leads to a wider particle size distribution and decreased performance in the final product.
[0006] Phase transformation and nucleation control are difficult: the transformation of alumina precursors (such as aluminum hydroxide, boehmite, etc.) into thermodynamically stable α-Al2O3 usually requires temperatures exceeding 1100℃. At such high temperatures, grains grow rapidly, making it difficult to obtain nanoscale α-phase particles, and sintering between particles is likely to occur.
[0007] To address the aforementioned issues, existing technologies have made some attempts. Chinese patent application CN117800372A, published on April 2, 2024, discloses a method for preparing high-purity nano-spherical alumina, but it still relies on a high-temperature, high-pressure hydrothermal reaction, and the particle size distribution of the final product needs further optimization. Chinese patent application CN114573013A, published on June 3, 2022, discloses a method for preparing spherical nano-alumina. Although the prepared alumina is nano-sized, the phase is γ-phase, and the particles are severely agglomerated, failing to obtain the desired thermally stable α-phase. Chinese patent application CN120589767A, published on September 5, 2025, discloses a method for preparing spherical nano-boehmite and spherical nano-alumina. Although spherical nano-alumina was obtained, electron micrographs show that the sintered particles still exhibit a certain degree of agglomeration. Chinese patent application CN111484050A, published on May 18, 2021, discloses a method for preparing spherical α-phase nano-alumina. By ball milling industrial alumina and adding sintering aids, there is still room for improvement in the sphericity and particle size control of the product.
[0008] Therefore, there is an urgent need in this field for a method that is simple in process, mild in production conditions, controllable in cost, and capable of producing high-quality near-spherical nano-α-alumina with small particle size, narrow distribution, high sphericity and low agglomeration, in order to meet the needs of high-end application markets. Summary of the Invention
[0009] In view of the shortcomings of the prior art, the purpose of this invention is to provide a method for preparing near-spherical nano-α-alumina, which aims to solve the problems of complex process, harsh reaction conditions, high calcination temperature, easy agglomeration of final product, and uneven particle size distribution in the existing preparation technology, so as to achieve a simple process, suitable for large-scale production, and able to stably prepare high-quality near-spherical nano-α-alumina.
[0010] Another objective of this invention is to provide a near-spherical nano-α-alumina with high sphericity, small particle size, and narrow distribution.
[0011] This invention is achieved using the following technical solution: The method for preparing the aforementioned nano-spherical alumina includes the following steps: a) Aluminum salt solution is mixed with a solution containing a precipitant and alumina seed crystals to carry out a precipitation reaction, thereby obtaining an alumina precursor; b) The alumina precursor is subjected to wet milling, and a morphology optimizer is added during or before the wet milling process to obtain a slurry; c) The slurry is dried and then calcined to obtain the spherical nano-α-alumina.
[0012] In step a), by controlling the conditions of the precipitation reaction (such as the type and concentration of aluminum salt and precipitant, reaction temperature, pH value, etc.), alumina precursors with different phases and morphologies can be prepared, such as amorphous aluminum hydroxide, boehmite, boehmite, or ammonium aluminum carbonate. This invention achieves "seed-induced nucleation" by pre-introducing alumina as a seed crystal into the precipitation reaction system. These added alumina nanoparticles, acting as the core of heterogeneous nucleation, provide numerous nucleation sites for the α-phase transformation during subsequent calcination. This significantly reduces the activation energy for α-phase formation, allowing the phase transformation to occur at lower temperatures. Simultaneously, the presence of the seed crystal can also regulate the microstructure of the precursor to a certain extent. Preferably, the amount of alumina seed crystal added is 1-10 wt% of the theoretical yield of α-alumina to be prepared; the alumina seed crystal is one or more of α, γ, θ, η, ρ, κ, χ, δ, and ε phases of alumina, preferably α-alumina or a mixed phase containing α-alumina.
[0013] Furthermore, to obtain a well-dispersed precursor, the solution containing the precipitant and alumina seeds described in step a) may also contain a dispersant. The dispersant prevents the aggregation of newly formed precursor particles through electrostatic repulsion or steric hindrance, laying the foundation for obtaining a monodisperse final product.
[0014] The aluminum salt is a soluble aluminum salt, preferably aluminum sulfate, aluminum nitrate, aluminum chloride, or ammonium aluminum sulfate; the precipitant is ammonia, urea, ammonium bicarbonate, and / or ammonium carbonate. This is a low-cost reaction system with easily manageable reaction byproducts. The reaction temperature is controlled within a mild range of 20-90℃, requiring no high-pressure equipment and facilitating industrial control.
[0015] In step b), the wet milling of the precursor is another key aspect of this invention. This step serves a dual purpose: firstly, the wet milling process effectively breaks down any soft agglomerates that may remain after filtration and washing, restoring the original particulate state of the precursor; secondly, and more importantly, wet milling allows the morphology modifier to be highly uniformly dispersed and coated on the surface of each precursor particle at the molecular or nanoscale level. This highly uniform distribution is difficult to achieve with traditional dry mixing methods.
[0016] The morphology optimizer consists of a fluoride, and optionally acid additives and / or inorganic ammonium salts. The fluoride is selected from at least one of aluminum fluoride, ammonium fluoride, calcium fluoride, magnesium fluoride, lithium fluoride, and zinc fluoride; the acid additives include at least one selected from boric acid, hydrochloric acid, nitric acid, sulfuric acid, citric acid, malic acid, oxalic acid, and acetic acid; the inorganic ammonium salt is selected from at least one of ammonium chloride, ammonium sulfate, ammonium carbonate, ammonium bisulfate, and ammonium nitrate. These substances act as "morphology optimizers" or "fluxants" during calcination. They can react with the precursor surface at lower temperatures or form a low-melting-point eutectic phase, promoting atomic diffusion and thus significantly reducing the phase transition temperature from γ-Al₂O₃ to α-Al₂O₃. Preferably, the amount of the morphology optimizer added is 0.5-5 wt% of the mass of the alumina precursor.
[0017] The wet grinding process can be completed within 15 minutes to 24 hours using high-efficiency grinding equipment such as sand mills or planetary ball mills, ensuring the full dispersion of the morphology optimizer.
[0018] The solution containing the precipitant and alumina seeds in step a) further contains a dispersant, which includes polymers, inorganic salts, and / or organic surfactants; wherein the organic surfactant is selected from at least one of polyethylene glycol, polyvinylpyrrolidone, sodium dodecyl sulfate, and organic ammonium salts; the organic ammonium salt includes at least one of alkyltrimethyl quaternary ammonium salt, hexadecyltrimethylammonium bromide (CTAB), and alkyldimethylbenzyl quaternary ammonium salt; and the inorganic salt is selected from sodium hexametaphosphate.
[0019] The morphology optimizer may be added during the precipitation reaction in step a), or during the wet milling process in step b), or in batches during steps a) and b). It is preferred to add it in step b).
[0020] In step c), calcination is performed. Due to the synergistic effect of seed induction in step a) and uniform dispersion of the morphology optimizer in step b), the present invention can significantly reduce the complete transformation temperature of the α phase to the range of 800-1300℃. Calcination at such a relatively low temperature (preferably 1-12 h) can effectively suppress abnormal grain growth and hard sintering between particles, thereby maximally preserving the spherical morphology of the precursor and ultimately obtaining nanoscale α-alumina with small and uniform particle size.
[0021] The near-spherical nano-α-alumina was prepared by the method described above.
[0022] Compared with the prior art, the beneficial effects of the present invention are: (1) Through the synergistic effect of alumina seed induction and morphology optimizer, the formation temperature of α-alumina was significantly reduced from the traditional above 1150℃ to the range of 900-1000℃, greatly reducing energy consumption and production costs. In the precipitation step, a uniform precursor was obtained by controlling the reaction conditions and using a dispersant; the key wet milling step ensured the microscopic uniform distribution of the morphology optimizer and avoided abnormal grain growth caused by local overheating or uneven additives during calcination. The lower calcination temperature effectively suppressed the sintering adhesion between particles, and finally obtained α-alumina powder with high sphericity, small particle size (nanoscale) and narrow distribution (good monodispersity).
[0023] (2) The present invention adopts precipitation reaction at normal temperature and pressure, followed by conventional filtration, washing, wet grinding, drying and calcination processes. The entire process does not require harsh conditions such as high temperature and high pressure or special and expensive equipment. The process route is mature and reliable, easy to control, and has the potential for large-scale industrial production. Attached Figure Description
[0024] Figure 1 This is a scanning electron microscope (SEM) image of the spherical nano-α-alumina prepared in Example 1 of the present invention.
[0025] Figure 2 The image shows the SEM image of the sample prepared in Comparative Example 1.
[0026] Figure 3 The image shows the SEM image of the sample prepared in Comparative Example 2.
[0027] Figure 4 The image shows the SEM image of the sample prepared in Comparative Example 3.
[0028] Figure 5 This is a SEM image of the sample prepared in Comparative Example 4.
[0029] Figure 6 This is a SEM image of the sample prepared in Comparative Example 5.
[0030] Figure 7 The image shows the XRD pattern of α-alumina obtained in Example 1 of this invention.
[0031] Figure 8 The image shows the XRD pattern of the sample prepared in Comparative Example 2.
[0032] Figure 9 This is a particle size distribution diagram of the near-spherical nano-α-alumina obtained in Example 1 of the present invention.
[0033] Figure 10 This is a SEM image of the aluminum ammonium carbonate precursor obtained in step (3) of Example 7 of the present invention before wet grinding.
[0034] Figure 11 This is a SEM image of the precursor slurry after drying following wet milling treatment in step (4) of embodiment 7 of the present invention. Detailed Implementation
[0035] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the scope of protection of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.
[0036] The "theoretical yield of α-alumina" mentioned in this invention refers to the theoretical mass of aluminum salt completely converted into α-Al₂O₃, calculated based on the amount of aluminum in the aluminum salt. Taking aluminum nitrate (Al(NO₃)₃·9H₂O, molecular weight 375.13) as an example, each mole can generate 0.5 moles of Al₂O₃ (molecular weight 101.96), so the theoretical yield = number of moles of aluminum salt × 0.5 × 101.96.
[0037] The main chemical reagents used in the embodiments and comparative examples of this invention and their sources are as follows: Ammonium aluminum sulfate ((NH4)Al(SO4)2·12H2O): Maclean's Reagent Company, analytical grade; Aluminum nitrate (Al(NO3)3·9H2O): Maclean's Reagent Company, analytical grade; Aluminum chloride (AlCl3·6H2O): Maclean's Reagent Company, analytical grade; Ammonium bicarbonate (NH4HCO3): Maclean's Reagent Company, analytical grade; Ammonium carbonate ((NH4)2CO3): Maclean's Reagent Company, analytical grade; Aluminum fluoride (AlF3): Maclean's Reagent Company, analytical grade; Calcium fluoride (CaF2): Maclean's Reagent Company, analytical grade; Polyethylene glycol-4000 (PEG-4000): Maclean's Reagents, analytical grade; Sodium hexametaphosphate: Maclean's Reagent Company, analytical grade; Boehmite (AlOOH): Maclean's Reagent Company, analytical grade; Zirconia spheres (Φ0.25-3mm, yttrium stable): Shandong Hanhe New Materials Co., Ltd. Nano-α-alumina powder: Chalco Shandong Co., Ltd.; Nano-γ-alumina powder: Chalco Shandong Co., Ltd.; Hexadecyltrimethylammonium bromide: Maclean's Reagent Company, analytical grade; Ammonium chloride: Maclean's Reagents, analytical grade.
[0038] The core technology of this invention, which discloses a method for preparing near-spherical nano-α-alumina, lies in the systematic and synergistic design and optimization of three key stages: precursor preparation, precursor post-treatment, and calcination. This allows for precise control over the phase, morphology, particle size, and dispersibility of the final product. The key steps and principles of this invention will be discussed in detail below.
[0039] The "quasi-spherical" shape described in this invention refers to the following: when observing at least 100 particles randomly selected by scanning electron microscopy (SEM), the aspect ratio (the ratio of the longest axis to the shortest axis of the particle) is calculated, with an average value between 1.0 and 1.5, and the particle outline is nearly circular or elliptical, without obvious sharp edges or corners.
[0040] Regarding step a): Preparation of alumina precursor by seed-induced precipitation This invention prepares alumina precursors via liquid-phase precipitation. By selecting different aluminum salts and precipitants, and controlling process parameters such as reaction temperature, pH, and concentration, aluminum hydroxide-based precursors with different phases and microstructures can be prepared. The universality of this invention lies in the fact that regardless of the specific phase of the precursor (such as amorphous aluminum hydroxide, boehmite, etc.), as long as its primary particles have a good near-spherical morphology and small size, it can serve as the morphological basis for obtaining the final near-spherical nano-α-alumina.
[0041] The key innovation of this step lies in the introduction of alumina seeds into the precipitation reaction system. This operation is based on the principle of "heterogeneous nucleation." In traditional seedless calcination, the phase transition from γ-Al₂O₃ to α-Al₂O₃ is homogeneous nucleation, requiring the overcoming of a very high nucleation energy barrier; therefore, the phase transition temperature is typically above 1100℃. In this invention, pre-added nano-sized alumina particles serve as ready-made nucleation sites. During calcination, the surrounding metastable alumina can directly undergo epitaxial growth on the surface of these seeds, forming the α-phase. This significantly reduces the activation energy for phase transition nucleation, allowing the phase transition to occur efficiently at a significantly lower temperature (e.g., 900-1000℃). The preferred amount of seed added is 1-10 wt% of the theoretical yield of the α-alumina to be prepared; too little will result in an insignificant induction effect, while too much may affect the overall performance of the final product and increase costs.
[0042] Furthermore, to ensure good dispersibility of the precursor particles during precipitation and avoid primary agglomeration, a dispersant is preferably added to the precipitant solution. The dispersant includes polymers, inorganic salts, and / or organic surfactants; wherein the organic surfactant is selected from at least one of polyethylene glycol, polyvinylpyrrolidone, sodium dodecyl sulfate, and organic ammonium salts; the organic ammonium salt includes at least one of alkyltrimethyl quaternary ammonium salt, hexadecyltrimethylammonium bromide (CTAB), and alkyldimethylbenzyl quaternary ammonium salt; and the inorganic salt is selected from sodium hexametaphosphate. Adsorption onto the surface of newly formed particles forms a steric hindrance layer or electrostatic repulsion layer, effectively preventing particles from approaching each other and agglomerating, thus laying the foundation for preparing a monodisperse final product.
[0043] The theoretical yield of α-alumina refers to the theoretical mass of aluminum salt completely converted into α-Al₂O₃, calculated based on the amount of aluminum in the aluminum salt. Taking aluminum nitrate nonahydrate (Al(NO₃)₃·9H₂O, molecular weight 375.13) as an example, each mole can generate 0.5 moles of Al₂O₃ (molecular weight 101.96). The theoretical yield = number of moles of aluminum salt × 0.5 × 101.96.
[0044] Regarding step b): wet milling treatment to achieve uniform loading of the morphology modifier. This step is another core feature that distinguishes this invention from the prior art. The purpose and effect of wet milling the dried alumina precursor (e.g., aluminum ammonium carbonate prepared using an ammonium carbonate system, abbreviated as AACH precursor) with a morphology optimizer far exceeds that of simple mixing.
[0045] First, wet milling is itself a highly efficient mechanochemical process. The high-speed moving grinding media (such as zirconia balls) exert strong shearing, impact, and grinding effects on the precursor particles, effectively breaking down the soft agglomerates formed during filtration and drying, and restoring the precursor to a state close to its original particles.
[0046] Secondly, and most importantly, wet milling ensures that the morphology optimizer is highly uniformly dispersed at the molecular or nanoscale level and firmly coated on the surface of each precursor particle. In this invention, the morphology optimizer acts as a "morphology optimizer" or "fluxant" during the calcination process. This morphology optimizer uses fluorides as its basic component and can be selectively compounded with acid additives (such as boric acid, hydrochloric acid, etc.) and / or inorganic ammonium salts (such as ammonium chloride, ammonium sulfate, etc.) as needed. These substances can react with the precursor surface at lower temperatures or form low-melting-point eutectics, producing a liquid phase or highly active surface, greatly promoting atomic migration and diffusion, thereby further reducing the α-phase transformation temperature. When inorganic ammonium salts are used in conjunction with fluorides, the inorganic ammonium salts may produce NH3 and HCl (or SO2, etc.) during thermal decomposition. These gaseous components can form a microenvironment on the particle surface, further promoting the mineralization of fluorides, or more effectively controlling the morphology and size of grains through a medium-assisted grain growth mechanism, thereby achieving complete α-phase transformation at lower temperatures and inhibiting abnormal grain growth. If traditional dry mixing is used, the additive particles and precursor particles only have point contact, resulting in extremely uneven distribution. During calcination, this can cause excessively high additive concentrations in some areas (leading to excessive particle growth or melting) while the concentrations in other areas are too low (incomplete phase transformation), ultimately resulting in a wide particle size distribution and poor morphology in the product. The wet milling process of this invention ensures that each precursor particle is coated with a uniform "morphology-optimizing agent shell," guaranteeing that all particles experience almost identical phase transformation conditions during calcination. This is a crucial foundation for obtaining a final product with uniform particle size and regular morphology. The preferred amount of morphology optimizer is 0.5-5 wt% of the precursor mass, so as to ensure the mineralization effect while avoiding the introduction of too many impurities.
[0047] When using a planetary ball mill for wet grinding, the diameter of the zirconia grinding balls is Φ0.5-3.0mm, the ball-to-material ratio is (5-15):1, the grinding speed is 200-500rpm, and the grinding media is anhydrous ethanol or deionized water with a solid content of 10-30wt%. When using a sand mill, the grinding speed is 500-3000rpm, the diameter of the grinding media (such as zirconia beads) is Φ0.25-3.0mm, the filling amount is 40%-80%, and the grinding time is 15min to 2h. Those skilled in the art can adjust within the above ranges according to the equipment type and target particle size.
[0048] Regarding step c): Low-to-medium temperature calcination This step is the final manifestation of the optimization effects of the first two steps. Due to the synergistic effect of seed induction in step a) and uniform loading of morphology optimizer in step b), the nucleation and growth processes of α-Al₂O₃ are effectively decoupled and controlled. Nucleation is mainly handled by the pre-placed seed crystals, while growth is carried out gently at a lower temperature with the assistance of the morphology optimizer. Therefore, this invention can significantly reduce the calcination temperature to 800-1300℃, particularly preferably in the "medium-low temperature" range of 900-1000℃. At such temperatures, the Brownian motion and sintering driving force of the grains are relatively weak, which can effectively suppress interparticle contact, neck formation, and final hard sintering, thereby maximally preserving the spherical morphology inherited from AACH and ultimately obtaining nanoscale α-alumina powder with small and uniform particle size.
[0049] When ammonium carbonate is used as a precipitant, the reaction temperature is preferably controlled between 20-60℃ to avoid excessive decomposition of the ammonium carbonate. When ammonium bicarbonate is used, the reaction temperature can be extended to 20-90℃.
[0050] To further clarify the operability of the present invention, boundary condition experiments were conducted: When the calcination temperature is below 800℃, even with the addition of seed crystals and morphology optimizers, the phase transformation of α-Al₂O₃ is still incomplete, and obvious γ or θ phase diffraction peaks remain in the XRD pattern. When the temperature is above 1300℃, the particles undergo significant hard sintering, the near-spherical morphology is destroyed, and the particle size increases sharply. Therefore, the preferred calcination temperature of this invention is 800-1300℃, and more preferably 900-1000℃.
[0051] When the pH of the precipitation reaction is below 6, some aluminum ions may not precipitate completely, leading to a decrease in yield. When the pH is above 12, the precursor crystallizes or agglomerates too quickly, resulting in a sharp increase in particle size and non-uniform morphology, which is not conducive to maintaining a spherical shape in subsequent processes. Therefore, in order to adapt to different aluminum salt and precipitant systems (generating amorphous aluminum hydroxide, boehmite, or ammonium aluminum carbonate, etc.), the pH of the precipitation reaction is preferably controlled between 6 and 12, and more preferably between 8 and 10.
[0052] When the amount of alumina seed crystals added is less than 1 wt% of the theoretical yield, the induced nucleation effect is insufficient, and the phase transformation temperature remains too high; when it is higher than 10 wt%, it has an adverse effect on product purity and cost. Therefore, the preferred amount of seed crystals added is 1-10 wt%. The alumina seed crystals are one or more of the α, γ, θ, η, ρ, κ, χ, δ, and ε phases of alumina, preferably α-alumina or a mixed phase containing α-alumina.
[0053] When the amount of morphology modifier added is less than 0.5 wt% of the precursor mass, the effect of reducing the phase transition temperature is not significant; when it is higher than 5 wt%, local melting or impurity phases are easily generated during calcination. Therefore, the preferred amount is 0.5-5 wt%.
[0054] The various phases of nano-alumina seed crystals used in the embodiments of the present invention can be obtained commercially or made in-house using conventional powder preparation processes. As long as their average particle size meets the nanoscale requirements (preferably less than 100 nm), they can be formulated into seed slurry for use.
[0055] In some improved embodiments of the present invention, the morphology optimizer is not limited to being added in the wet milling step; it can also be added together with the seed crystals in the precipitation reaction step (step a), or added in batches before, during, and after the wet milling process. Experiments show that adding morphology optimizers such as aluminum fluoride in advance in the precipitation step, or adding them step by step during the wet milling process, can both achieve the preparation of near-spherical nano-α-alumina, but the particle morphology obtained by uniform coating during the wet milling process is the most uniform. This flexible addition method allows for further optimization of the process based on actual production needs and precursor characteristics without changing the core principle of the present invention, in order to obtain the best product performance. These variations are all within the scope of protection of the present invention.
[0056] In summary, this invention is not a simple aggregation of process steps, but a systematic solution with interconnected and mutually reinforcing steps. Through the technical path of "preferred precursor → seed-induced nucleation → wet milling for uniform loading of morphology-optimizing agent → low-temperature synergistic calcination," it successfully resolves the core contradiction between "low-temperature phase transformation" and "morphology preservation" in the preparation of near-spherical nano-α-alumina.
[0057] The technical solution and beneficial effects of the present invention will be further illustrated below through specific embodiments and comparative examples.
[0058] Example 1 This embodiment provides a method for preparing spherical nano-α-alumina with a particle size of approximately 120 nm. The specific steps are as follows: (1) Dissolve 18.76g of aluminum nitrate (Al(NO3)3·9H2O) in 500mL of deionized water to prepare an aluminum nitrate solution A with a concentration of 0.1M. Take another 500mL of deionized water as the reaction medium, add polyethylene glycol-4000 as a dispersant accounting for 5wt% of the theoretical alumina yield, and α-alumina seed slurry (average particle size D50 of about 80nm) accounting for 3wt% of the theoretical alumina yield, and stir magnetically at 40℃.
[0059] (2) Solution A and 1.0M ammonia solution were added dropwise to the reaction medium in parallel using a peristaltic pump at a rate of 5 mL / min and a variable rate, respectively. The pH of the reaction system was monitored and controlled in real time using a pH meter to keep it stable at 9.0. The reaction system was kept at a constant temperature of 40℃ and stirred continuously for 12 h to obtain an aluminum hydroxide precursor suspension.
[0060] (3) The suspension obtained in step (2) was filtered and washed with deionized water until neutral. The resulting filter cake was dried in an oven at 80°C for 12 hours to obtain alumina precursor powder.
[0061] (4) Take 10g of the precursor powder obtained in step (3), add 0.2g (2wt% of the precursor mass) of aluminum fluoride (AlF3) as a morphology optimizer, and add 50mL of anhydrous ethanol as a grinding medium. Transfer the mixture to a 100mL zirconia planetary ball mill jar, use zirconia balls as grinding balls (ball-to-material ratio 10:1), and wet mill at 400rpm for 12h.
[0062] (5) The slurry obtained in step (4) is dried in an oven at 80°C for 12 hours to obtain a precursor powder uniformly loaded with morphology optimizer. The powder is placed in a muffle furnace and heated to 1000°C at a rate of 5°C / min, held at that temperature for 3 hours, and then naturally cooled to obtain spherical nano-α-alumina powder.
[0063] The scanning electron microscope (SEM) image of the near-spherical nano-α-alumina obtained in Example 1 is shown below. Figure 1 The XRD pattern of α-alumina obtained in Example 1 is shown in [reference needed]. Figure 7 The particle size distribution diagram of the near-spherical nano-α-alumina obtained in Example 1 is shown in the figure. Figure 9 .
[0064] Example 2 This embodiment is basically the same as embodiment 1, except that: In step (1), the amount of α-alumina seed crystals added is 1 wt% of the theoretical yield of alumina.
[0065] In step (4), the amount of morphology optimizer aluminum fluoride (AlF3) added is 3 wt% of the precursor mass.
[0066] In step (5), the calcination temperature is 900℃ and the holding time is 2h.
[0067] Example 3 This embodiment is basically the same as embodiment 1, except that: In step (1), the dispersant is replaced with an equal mass of sodium hexametaphosphate, and the reaction temperature is 60℃.
[0068] In step (4), the morphology optimizer is replaced with ammonium fluoride (NH4F) at 2 wt% of the precursor mass.
[0069] In step (5), the calcination temperature is 1000℃ and the holding time is 3h.
[0070] Example 4 This embodiment is basically the same as embodiment 1, except that: In step (1), the amount of α-alumina seed crystals added is 10 wt% of the theoretical yield of alumina, and the reaction temperature is 90℃.
[0071] In step (5), the calcination temperature is 1250℃ and the holding time is 1h.
[0072] Example 5 This embodiment is basically the same as embodiment 1, except that: In step (1), the precipitant was replaced with ammonium bicarbonate. The ammonium bicarbonate was dissolved in deionized water to prepare a 1.0 M solution. The ammonium bicarbonate solution and the aluminum salt solution were added dropwise to the reaction medium in parallel using a peristaltic pump. The reaction temperature was controlled at 30°C, and the pH of the reaction system was stabilized at 9.0 by adjusting the dropping rate. With all other conditions unchanged, the morphology of the resulting quasi-spherical nano-α-alumina was similar to that of Example 1, with uniform particle size distribution and an α-phase conversion rate ≥95%.
[0073] Example 6 This embodiment is basically the same as embodiment 1, except that: In step (1), the precipitant was replaced by an equimolar amount of ammonium carbonate. The ammonium carbonate was dissolved in deionized water to prepare a 0.5M solution, which was then added dropwise to the reaction medium along with the aluminum nitrate solution. The reaction temperature was controlled at 30°C, and the pH of the reaction system was stabilized at 9.0 by adjusting the dropping rate. The resulting precursor had good morphology, and after calcination, the α-alumina was spherical with excellent dispersibility.
[0074] Example 7 This embodiment is basically the same as embodiment 1, except that: In step (1), aluminum nitrate is replaced with an equimolar amount of ammonium aluminum sulfate ((NH4)Al(SO4)2·12H2O), and the precipitant is replaced with an ammonium bicarbonate (NH4HCO3) solution of the corresponding concentration. The reaction temperature is 30℃.
[0075] In step (4), the amount of morphology optimizer aluminum fluoride (AlF3) added is 1 wt% of the precursor mass, and the wet milling time is 24 h.
[0076] In step (5), the calcination temperature is 950℃ and the holding time is 4h.
[0077] With other conditions remaining unchanged, the resulting spherical nano-alumina particles have a diameter of approximately 100 nm, maintain good morphology, and exhibit excellent dispersibility.
[0078] Example 8 This embodiment is basically the same as embodiment 1, except that: In step (1), aluminum nitrate was replaced with an equimolar amount of aluminum chloride (AlCl3·6H2O), ammonium bicarbonate was used as the precipitant, and the reaction temperature was 30℃. All other conditions remained unchanged. The resulting near-spherical nano-α-alumina had an α-phase conversion rate of 95.8%, a D50 of 188 nm, a Span of 2.15, and exhibited a near-spherical morphology with good dispersibility.
[0079] Example 9 This embodiment is basically the same as embodiment 1, except that: In step (4), aluminum fluoride was replaced with magnesium fluoride (MgF2) at 2 wt% of the precursor mass. All other conditions remained unchanged. The resulting α-alumina had an α-phase conversion rate of 92.7%, a D50 of 142 nm, a Span of 2.28, and maintained a near-spherical morphology.
[0080] Example 10 This embodiment is basically the same as embodiment 1, except that: In step (1), the dispersant is replaced by an equal mass of an ammonium salt organic surfactant, cetyltrimethylammonium bromide (CTAB), and the pH of the reaction medium is controlled at 8.0.
[0081] The remaining steps and conditions are consistent with those in Example 1.
[0082] The resulting nano-α-alumina powder, observed by SEM, exhibited uniform, near-spherical particles with a D50 of approximately 146 nm and excellent dispersibility. This demonstrates that the use of ammonium salt surfactants can effectively leverage the synergistic effect of steric hindrance and electrostatic repulsion to prevent precursor aggregation.
[0083] Example 11 This embodiment is basically the same as embodiment 1, except that: In step (4), the wet milling treatment method for the precursor and morphology optimizer was adjusted. The wet milling equipment was replaced with a horizontal sand mill, the grinding media were 0.3 mm diameter zirconia beads, the grinding speed was set to 2500 rpm, and the grinding time was 30 min.
[0084] The remaining steps and conditions are consistent with those in Example 1.
[0085] The final sample exhibited an α-phase conversion rate ≥96%, and the particles maintained a good near-spherical morphology. This indicates that high-energy sand milling using small-sized grinding media can achieve molecular-level uniform coating of morphology optimizers on the particle surface in a very short time (e.g., within 15 min to 2 h), significantly improving production efficiency.
[0086] Example 12: This embodiment is basically the same as embodiment 1, except that in step (1), the α-alumina seed crystal is replaced with a mixed nano-alumina seed crystal with a mass ratio of 1:1 between the α phase and the θ phase.
[0087] Example 13: This embodiment is basically the same as that of embodiment 1, except that: in step (4), the amount of morphology optimizer aluminum fluoride (AlF3) added is 5wt% of the precursor mass; in step (5), the calcination temperature is 800℃ and the holding time is 12h.
[0088] Example 14: This embodiment is basically the same as that of embodiment 1, except that in step (4), the morphology optimizer is replaced with a composition of aluminum fluoride and boric acid (mass ratio 1:1) accounting for 2 wt% of the precursor mass.
[0089] Example 15: This embodiment is basically the same as that of embodiment 1, except that in step (4), the morphology optimizer is replaced with a composition containing aluminum fluoride, 1M dilute hydrochloric acid and ammonium chloride (mass ratio of 2:1:1), and the total amount added is 2wt% of the precursor mass.
[0090] Example 16: This embodiment is basically the same as that of embodiment 1, except that in step (4), the morphology optimizer is replaced with a composition of aluminum fluoride and calcium fluoride (mass ratio 1:1) accounting for 2wt% of the precursor mass.
[0091] Comparative Example 1: Except for the following differences, the remaining steps are exactly the same as in Example 1: steps (1)-(3) of Example 1 are not performed; instead, commercially available boehmite (AlOOH) powder is used directly as a precursor, and steps (4) and (5) of Example 1 are performed. In step (4), the same type and amount of seed crystals as in Example 1 are added, that is, the boehmite is wet-milled and blended with aluminum fluoride and then calcined. The SEM image of the sample obtained in Comparative Example 1 is shown below. Figure 2 .
[0092] Comparative Example 2: Except for the following differences, the remaining steps are exactly the same as in Example 1: in step (1), no α-alumina seed crystals are added, and all other conditions and operations remain unchanged. The SEM image of the sample obtained in Comparative Example 2 is shown below. Figure 3 The XRD pattern of the sample prepared in Comparative Example 2 is shown in the figure. Figure 8 .
[0093] Comparative Example 3: Except for the following differences, the remaining steps are exactly the same as in Example 1: In step (4), aluminum fluoride (AlF3) is not added, and only the AACH precursor is wet-milled.
[0094] In step (5), to ensure complete transformation into the α phase, the calcination temperature is increased to 1200℃ and held for 2 hours.
[0095] SEM images of the samples prepared in Comparative Example 3 are shown below. Figure 4 .
[0096] Comparative Example 4: Except for the following differences, the remaining steps are exactly the same as in Example 1: the wet milling process in step (4) is replaced by: dry mixing 10g of AACH powder and 0.1g of aluminum fluoride powder in a V-type mixer for 1h. The SEM image of the sample obtained in Comparative Example 4 is shown below. Figure 5 .
[0097] Comparative Example 5: The difference between this comparative example and Example 1 is that the type of seed crystal added in step (1) is different, while the rest of the steps are the same as in Example 1.
[0098] Specifically, in step (1), instead of adding α-alumina seeds, γ-alumina seeds (average particle size D50 of approximately 80 nm) accounting for 3 wt% of the theoretical alumina yield were added, while other conditions remained exactly the same as in Example 1. The SEM image of the sample obtained in Comparative Example 5 is shown below. Figure 6 .
[0099] Comparative Example 6 The difference between this comparative example and Example 1 is that the wet milling conditions in step (4) have insufficient energy; the remaining steps are the same as in Example 1. The specific steps are as follows: (1)-(3) are the same as steps (1)-(3) in Example 1, to obtain alumina precursor powder.
[0100] (4) Take 10g of the precursor powder obtained in step (3), add 0.2g (2wt% of the precursor mass) of aluminum fluoride (AlF3) as a morphology optimizer, and add 50mL of anhydrous ethanol as a grinding medium. Transfer the mixture to a 100mL zirconia planetary ball mill jar, use zirconia balls as grinding balls (ball-to-material ratio 10:1), and perform wet milling at a low speed (200rpm) for 30min.
[0101] (5) The slurry obtained in step (4) is dried in an oven at 80°C for 12 hours to obtain precursor powder. The powder is placed in a muffle furnace and heated to 1000°C at a rate of 5°C / min, held at that temperature for 3 hours, and then naturally cooled to obtain alumina powder.
[0102] The powders obtained in Examples 1-16 and Comparative Examples 1-6 were characterized in terms of performance, and the test methods are as follows: Phase analysis: The phases of the sample were identified using X-ray diffraction (XRD), and the phase transformation rate of α-Al2O3 was semi-quantitatively calculated using RIR.
[0103] Morphological observation: The particle morphology, dispersion state and agglomeration of the powder were observed using a scanning electron microscope (SEM).
[0104] Particle size analysis: The secondary particle size distribution (D10, D50, D90) of the powder was tested using a laser particle size analyzer, and the particle size distribution width Span value was calculated (Span = (D90-D10) / D50).
[0105] The test data for Examples 1-16 and Comparative Examples 1-6 are shown in Table 1.
[0106] Table 1: Test data of Examples 1-16 and Comparative Examples 1-6
[0107] Through Table 1 and Figure 1-11 The obtained data shows that, through Figure 1It can be seen that the alumina prepared by the method in Example 1 exhibits a near-spherical morphology with high sphericity, uniform particle size, and an average particle size of approximately 120 nm. Table 1 shows the α-conversion rate, particle size distribution, and morphology observation and evaluation of alumina prepared by different examples and comparative examples. This demonstrates that the morphology, α-conversion rate, and particle size distribution of the prepared alumina can be directionally adjusted through a series of raw material selections and process parameter controls, further demonstrating the excellent universality of the present invention and its potential for large-scale industrial production. A comparison of Example 1 with Comparative Examples 1 and 2 illustrates the necessity of adding seed crystals during the precipitation process. Without the addition of seed crystals, the obtained alumina particles have a grain size of approximately 1 μm. In other processes, the addition of seed crystals has limited grain refinement effect, resulting in large and uneven alumina particles. Furthermore, through comparison... Figure 7 and Figure 8 This demonstrates that the addition of seed crystals can further reduce the sintering temperature of alumina, allowing it to transform into the α phase at 900℃, making the production process more economical and energy-efficient. A comparison between Example 1 and Comparative Example 3 shows the necessity of morphology optimizers; without them, the resulting alumina can hardly form a spherical morphology, with most particles exhibiting a worm-like shape and severe sintering agglomeration. A comparison between Example 1 and Comparative Example 4 demonstrates the necessity of the wet grinding process. Figure 10 and Figure 11 The images show the precursor morphology before and after wet milling. It can be seen that the precursor morphology changed after wet milling, forming a loose, porous structure. This structure helps to better utilize the gaseous products of the morphology optimizer to achieve morphology optimization. In contrast, the alumina obtained in Comparative Example 4 only partially transformed into a spherical morphology, still exhibiting some worm-like structures and sintering agglomeration. A comparison between Example 1 and Comparative Example 5 demonstrates the advantage of α-alumina as a preferred seed crystal. The alumina grain size obtained using γ- and θ-mixed alumina as seed crystals is around 500 nm, smaller than the alumina obtained in Comparative Example 2 but larger than the alumina obtained in Example 1. This indicates that γ-alumina as a seed crystal can refine grains, but the effect is limited. A comparison between Example 1 and Comparative Example 6 demonstrates the necessity of sufficient wet milling time. Although the particles in Comparative Example 6 are also mostly spherical with a size of about 150 nm, the overall particle size is relatively uneven, with some spherical particles of 300-500 nm and 50-100 nm in size. This indicates that under insufficient wet milling conditions, the morphology modifier cannot be uniformly distributed in the precursor. Therefore, small particles are obtained where the concentration of the morphology modifier is high in the macroscopic space, while large particles are obtained where the concentration is low.
Claims
1. A method for preparing near-spherical nano-α-alumina, characterized in that, Includes the following steps: a) Aluminum salt solution is mixed with a solution containing a precipitant and alumina seed crystals to carry out a precipitation reaction, thereby obtaining an alumina precursor; b) The alumina precursor is subjected to wet milling, and a morphology optimizer is added during or before the wet milling process to obtain a slurry; c) The slurry is dried and then calcined to obtain the spherical nano-α-alumina; The morphology optimizer consists of fluorides, and optionally acid additives and / or inorganic ammonium salts; The fluoride is selected from at least one of aluminum fluoride, ammonium fluoride, calcium fluoride, and magnesium fluoride; The acid additives include at least one selected from boric acid and hydrochloric acid; The inorganic ammonium salt is selected from at least one of ammonium chloride and ammonium sulfate; In step a), the amount of alumina seed crystals added is 1-10 wt% of the theoretical yield of α-alumina to be prepared; the alumina seed crystals are α-alumina or a mixed phase containing α-alumina; The precipitation reaction described in step a) is carried out at a temperature of 20-90℃ and a pH of 8-10.
2. The method for preparing near-spherical nano-α-alumina according to claim 1, characterized in that, The aluminum salt is a soluble aluminum salt; the precipitant is at least one of ammonia, urea, ammonium bicarbonate, and ammonium carbonate.
3. The method for preparing near-spherical nano-α-alumina according to claim 1, characterized in that, The solution containing the precipitant and alumina seeds in step a) further contains a dispersant, which includes polymers, inorganic salts, and / or organic surfactants; wherein the organic surfactant is selected from at least one of polyethylene glycol, polyvinylpyrrolidone, sodium dodecyl sulfate, and organic ammonium salts; the organic ammonium salt includes at least one of alkyltrimethyl quaternary ammonium salt, hexadecyltrimethylammonium bromide, and alkyldimethylbenzyl quaternary ammonium salt; and the inorganic salt is selected from sodium hexametaphosphate.
4. The method for preparing near-spherical nano-α-alumina according to claim 1, characterized in that, The amount of the morphology optimizer added is 0.5-5 wt% of the mass of the alumina precursor.
5. The method for preparing near-spherical nano-α-alumina according to claim 1, characterized in that, The wet grinding process described in step b) is carried out using a sand mill or a planetary ball mill.
6. The method for preparing near-spherical nano-α-alumina according to claim 5, characterized in that, The wet milling process described in step b) takes 15 minutes to 24 hours. The calcination temperature in step c) is 800-1300℃, and the calcination time is 1-12h.
7. A quasi-spherical nano-α-alumina, characterized in that, It is prepared by the method for preparing near-spherical nano-α-alumina according to any one of claims 1-6.
Citation Information
Patent Citations
Preparation method of sphere-like alpha-phase nano aluminum oxide
CN111484050A
Preparation method of sphere-like nano aluminum oxide
CN114573013A
High-purity nano sphere-like aluminum oxide and preparation method thereof
CN117800372A
Preparation method of sphere-like nano boehmite and sphere-like nano aluminum oxide
CN120589767A
Preparation method of microcrystal spheroidic alumina powder
CN114940505A